Effect of errorless learning on the acquisition of fine motor skills in pre‐clinical endodontics. (28th November 2020) - El‐Kishawi, Mohamed; Khalaf, Khaled; Masters, Rich; Winning, Tracey
Abstract: This study aimed to evaluate the impact of errorless and errorful learning, on acquisition of root canal hand‐instrumentation skills. Dental students prepared standardised canals of different diameters and curvatures. Learning involved minimising (errorless: n  = 21) or maximising errors (errorful: n  = 21). Students who had completed accredited pre‐clinical activities provided comparative data ( n  = 17). During testing, the distal canal of a plastic mandibular molar was prepared, first as a single task and then under multi‐tasking conditions. Performance was assessed by preparation accuracy and time. Differences were assessed using anova ( P  < 0.05). Performance in the experimental groups was similar during learning. When multi‐tasking, errorful learners showed a deterioration in preparation accuracy ( P  < 0.05). In contrast, preparation accuracy and completion times for the errorless and comparative groups remained stable when multi‐tasking. Errorless learning resulted in stable performance under multi‐tasking conditions. Investigation of alternative approaches to learning motor skills in dentistry is warranted as such approaches may provide better outcomes, especially under demanding conditions.